Evaluation of the Implementation of E-Government Public Service Aduan Konten Using E-Govqual, Importance Performance Analysis and Heuristic Evaluation (case study: Ministry of Communication and Information, APTIKA directorate) - Nila Rusiardi Jayanti; Gerry Firmansyah; Nenden Siti Fatonah; Budi Tjahjono; Habibullah Akbar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the current condition of society that is critical in responding to everything, more public services are needed professional, effective, simple, transparent, timely, responsive. Efforts to improve the quality of public services cannot be separated from service evaluation. In order to improve the quality of public services, the Directorate General of Informatics Applications of the Ministry of Communications and Informatics established the Public Service for Aduan konten at the Directorate of Information Application Control (PAI) as a pilot project. So to evaluate the quality of public services, a bureaucratic reform program is carried out at the PAI Directorate through efforts to develop a zone of territorial integrity free from corruption and a clean bureaucratic area to serve. One of the evaluations carried out is for measuring service performance as mandated in the Regulation of the Minister of Administrative Reform Number 14 of 2017 concerning the Community Satisfaction Survey (SKM) on the Implementation of Public Services. This study aims to determine the service quality of the Content Complaint website using the e-Govqual method, while the IPA and heuristic evaluations are to determine the attributes that are priorities for improving service quality, as recommendations to public service providers for Aduan konten. To assess the service quality of the content complaint website, 6 dimensions and 21 e-Govqual attributes are used. Of the 300 respondents who were used as research samples, this study shows the results of the analysis of the level of conformity of the 6 dimensions are 98.03% (<100%) meaning that the public services provided by the Aduan konten website are not satisfactory to users or still not in accordance with user expectations. The result of the average value of the gap between expectations and performance shows the number -0.05 or < 0. With this gap, it can be said that the quality of public service performance of Aduan konten perceived by the public still does not meet what is expected. Attributes that need improvement are those in quadrant A (3 attributes) and quadrant C (8 attributes). Recommendations are given based on the literature/theory for attributes that need to be improved to improve the quality of public services for Aduan konten.